A 16-Step Total Synthesis of Norzoanthamine - Zhang, Weiyue; Zhang, Xiao; Sun, Yuchen; Sun, Yu (Synlett, 2025)
Herein, we present a 16-step synthetic route to norzoanthamine that features three pivotal photochemical transformations. A photoinduced dearomative 6π-desymmetrization is employed to access the ABC tricyclic core structure. To address the challenge of constructing the C9–C22 vicinal all-carbon quaternary stereocenters, [2+2]-photocycloaddition, visible-light-induced decarboxylative borylation, and a retro-aldol reaction are strategically employed. The assembly of the norzoanthamine core framework is achieved through a one-pot cascade transformation, combining global deprotection, biomimetic cyclization, and epimerization at C21, resulting in an efficient and concise synthesis of norzoanthamine.1 Introduction2 Total Synthesis of Norzoanthamine3 Conclusion
Keywords: norzoanthamine; total synthesis; marine alkaloids; photocycloaddition; anti-osteoporosis